Role of Women Entrepreneurship in Reduction of Social Norms for Sustainable Development (Journal of Informatics Education and Research, 2024)
The issue of sustainable development has garnered considerable interest from researchers and professionals who are deeply invested in environmental concerns. Sustainable development has emerged as a significant subject in environmental discourse. The significance of entrepreneurship in addressing sustainable development challenges, alongside innovation. Entrepreneurship has garnered significant attention across scientific disciplines for its role in driving sustainable development. This study investigates the potential influence of entrepreneurship on sustainable development, with a specific emphasis on its economic, environmental, and social aspects. Through a structured survey instrument administered using five-point Likert’s scale inferential statistical methods like the Chi-square test and the ANOVA test are used to identify significant predictors of women's empowerment within the context of social norms. This study aims to offer empirical evidence and actionable insights into the intricate interplay between social norms, sustainable development and women's empowerment in entrepreneurship, contributing to a deeper understanding of this critical area. The finding indicates that there is a significant effect on women's empowerment influence women's decision to engage in social network.